Partisipasi Politik Perempuan Menurut Fatima Mernissi dan Relevansinya dengan Affirmative Action di Indonesia - Nuril Hidayati; Ellyda Retpitasari (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2019)
Abstract: This article will discuss Fatima Mernissi’s thought on the importance of involving women’s participation in the political realm, as an important way of fighting for gender equality in the Muslim countries, including Indonesia where women’s political participation is low. According to Mernissi, to achieve equality the government must increase the capacity of women’s leadership. So the women can participate actively and enjoy their human rights in the country. This study shows that despite law in Indonesia No. 10 2008 concerning the elections for DPR, DPD and DPRD, article 8 paragraph 1 letter d stating that “political parties can participate in the election after fulfilling the requirements to include at least 30% representation of women in the management of central political parties” known as affirmative action, does not appear to have a significant impact on the level of women’s political participation in Indonesia. According to Mernissi’s thought, this condition may be caused by the problem of the authority of religious interpretation about the women’s participation in the public sphere.